Anticipating Disaster: The ‘Urf Perspective of Rebo Wekasan Ceremony in Kudus, Central Java - Moh Rosyid; Lina Kushidayati (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
Rebo Wekasan is a popular practice among Indonesian Muslims, including those who live in Kudus, Central Java. This article discusses the practice of Rebo Wekasan in Indonesia generally, Kudus in specific, and the rite of drinking water salamun, as well as the practice of Rebo Wekasan from the perspective of 'urf. The anthropological approach is used to understand the tradition of Rebo Wekasan while the observation took place in 2021. Additionally, we also collected relevant documents including pictures and newspaper articles of Rebo Wekasan from 2018 to 2019, and interviews with 8 resource persons ranging from takmir (caretaker of the mosque), ceremonial committee, village officials, and visitors. Rebo Wekasan rite in Kudus is done by performing sholat tolak bala (prayer for anticipating any calamities) and drinking salamun (blessing-infused) water. People who attend the ceremony believe it based on religious belief and classic text showing that the last Wednesday in Safar month is the day of disaster advent. They also believe in the Javanese value that water is a medium of spiritual cleansing. In the perspective of 'urf (custom), Rebo Wekasan is deemed to fulfill aspects of ‘urf belonging to the category of 'urf shahih (good custom) because it contains noble values and is sourced from religious teaching.